Experimental study on the noise reduction of hydraulic bench - Muhammad Saufi, Abdul (2010)
This report is the result of a research on undergraduate project of Experimental Study on the Noise Reduction of Hydraulic Bench. The hydraulic bench is used to study the performance of fluids and the hydraulic theory. This report presents the noise source identification and noise reduction at hydraulic bench. The identification of the main source of noise must be done first before the noise reduction is done at hydraulic bench because the noise reduction will do based on the part that produce the main source of noise at hydraulic bench. Many method can be use for noise reduction process but in this research, the egg tray and fibre is used as material to reduce noise from hydraulic bench. The egg tray is use only for shaped the fibre to get more surface absorption. In this project, the result is achieved by using PULSE LABSHOP (Intensity Mapping). In intensity mapping, the colour contour represents the sound power. Comparison of result before and after noise reduction was conducted. The result from the experiment show that the main source of noise is at hydraulic pump and the noise from the hydraulic bench can be reduce up to 15 dB.